2003
DOI: 10.1074/jbc.m300003200
|View full text |Cite
|
Sign up to set email alerts
|

ATP Activates Ataxia-Telangiectasia Mutated (ATM) in Vitro

Abstract: Ataxia-telangiectasia Mutated (ATM), mutated in the human disorder ataxia-telangiectasia, is rapidly activated by DNA double strand breaks. The mechanism of activation remains unresolved, and it is uncertain whether autophosphorylation contributes to activation. We describe an in vitro immunoprecipitation system demonstrating activation of ATM kinase from unirradiated extracts by preincubation with ATP. Activation is both time-and ATP concentration-dependent, other nucleotides fail to activate ATM, and DNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 57 publications
4
62
0
Order By: Relevance
“…This lack of requirement for autophosphorylation for activation in vitro was similar to that reported earlier by Bakkenist and Kastan (2003). Indeed, there are several reports of ATM activation in vitro and in vivo without the requirement for S1981 autophosphorylation (Kozlov et al, 2003;Hamer et al, 2004;Powers et al, 2004).…”
Section: Viral Infection and In Vitro Models To Investigate The Role supporting
confidence: 87%
See 2 more Smart Citations
“…This lack of requirement for autophosphorylation for activation in vitro was similar to that reported earlier by Bakkenist and Kastan (2003). Indeed, there are several reports of ATM activation in vitro and in vivo without the requirement for S1981 autophosphorylation (Kozlov et al, 2003;Hamer et al, 2004;Powers et al, 2004).…”
Section: Viral Infection and In Vitro Models To Investigate The Role supporting
confidence: 87%
“…Evidence using rare genetic disorders and mouse models While the recruitment of the MRN complex to damaged DNA is rapid, so too is the activation of ATM (Bakkenist and Kastan, 2003;Kozlov et al, 2003), making it difficult to discern the sequence of events involved. If the MRN complex were the sensor of DNA breaks then it might be expected that it would be upstream of ATM activation.…”
Section: Atm Is Recruited To and Activated By The Mrn Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, Bakkenist and Kastan (2003) showed that autophosphorylation of ATM after DNA damage is required for monomerization. Immunoprecipitated ATM was also shown to be autophosphorylated in vitro during incubation with g 32 -ATP, and the preincubation with ATP correlated with higher levels of kinase activity in vitro (Kozlov et al, 2003). Later, other phosphorylation sites on ATM were found in addition to Ser1981, including Ser367 and Ser1893 (Kozlov et al, 2006).…”
Section: Atm Autophosphorylationmentioning
confidence: 91%
“…What is clear is that divalent cations such as Mn 2 þ stimulate the in vitro kinase activity of ATM, perhaps by mimicking the effect of DNA on ATM (Durocher and Jackson, 2001;Jackson, 2001). Recently, two studies showed that ATM autophosphorylation is important for the activation of the associated kinase (Bakkenist and Kastan, 2003;Kozlov et al, 2003). It was proposed that ATM is sequestered in unperturbed cells as a dimer with its kinase domain interacting with an internal domain of a neighboring ATM molecule spanning S1981 (Bakkenist and Kastan, 2003).…”
Section: Atm Targets Involved In Dsb Repairmentioning
confidence: 99%